Corporate recruitment practices and the hierarchy of graduate employability in India. (2nd January 2020) - Sadik, Sahara; Brown, Phillip
ABSTRACT: Policy and academic circles in India put forth the argument that the country's demographic dividend puts it in an optimal position to win the race between education and technology across nations by expanding higher education opportunities. This article examines the recruitment practices of 13 leading corporations in high-growth sectors in India. Based on detailed qualitative interviews, it explains why these corporations are unlikely to increase the demand for graduates in ways imagined by policy-makers or proponents of skills-biased technological change. Companies in India are locked into an intense 'war for talent', but only for graduates in India's top-tier universities. We argue that there is a close correspondence between India's highly elitist university system and corporate talent management strategies, creating a narrow pool of highly mobile Indian corporate elite, but resulting in limited prospects for the wider Indian workforce. In this talent market, the success of the top corporate elite rests on keeping the elitist character of higher education, rather than widening labour market opportunities. This paper also seeks to explain why top corporations in India engage in this 'war for talent' when they are not always certain their investments pay off.